Effects of Different Ion Erosion on the Hydration Mechanism and Microstructure of Nano-Clay Single-Liquid Grouting Material - Hong, Zi-jie; Zuo, Jian-ping (Frontiers in Physics, 2022)
Abstract: The effect of nano-clay (NC) on hydration and microstructure of grouting material was investigated under different ion erosion. Different erosion conditions and six different content of NC specimens were prepared. This paper investigated the influence of NC on the mechanical properties and microstructure of cement material under chloride ion erosion and standard curing condition (SCC), using ultrasonic pulse velocity (UPV), uniaxial compressive strength (UCS), fourier transform infrared spectroscopy (FT-IR) and scanning electron microscope (SEM). The experimental results demonstrated that the nano-core effect can promote the formation of the core reaction of grouting material and accelerate the hydration process. With the additional NC, the hydration products of ettringite (AFt) and calcium silicate hydrate (C-S-H) are increased. Under the chloride ion erosion, it was obtained that when the additional NC was less than 2%, the UCS and UPV were improved. As NC content is 2%, hydration reaction is the most adequate, mechanical properties and erosion resistance are the best. However, under high humidity condition, as NC content is 1%, the amount and density of AFt is increased, the formation of C-S-H gel is most. The hydration reaction was inhibited and the mechanical properties of grouting materials decreased when NC was further increased. It indicated that the complex underground engineering environment affected the hydration mechanism of nano-grouting material.